Internal fixation of proximal humeral fractures with a Polarus humeral nail - Koike, Yoichi (Springer Milan, 2008)
BACKGROUND: Proximal humeral fractures occur frequently. Displaced or unstable fractures require open reduction and internal fixation. Our objective was to investigate the clinical and radiographic results of the internal fixation using Polarus humeral nails for fractures of the proximal humerus. MATERIALS AND METHODS: From January 2001 to April 2006, 54 shoulders of 54 patients (44 females, 10 males) underwent the intramedullary fixation using Polarus humeral nail. Mean age of the patients was 66-year-old (39–89) at the time of the surgery. Fracture-type by Neer classification was 2-part (29 shoulders), 3-part (22 shoulders) and 4-part (3 shoulders). The clinical and radiological outcomes were evaluated. RESULTS: All the shoulders after osteosynthesis obtained bone-union. There was no osteonecrosis of the humeral head. Functional outcome measured by JOA score averaged 81 points. Totally 43 patients (79%) had satisfactory to excellent results. Varus deformity was seen in 4 shoulders (8%) and the deformity of the greater tuberosity in 4 (8%). CONCLUSION: The Polarus intramedullary humeral nail is effective for the treatment of proximal humeral fractures.